DC-DC Converter Design Issues for High-Efficient DC Microgrid - Frivaldsky, Michal; Morgos, Jan (Communications - Scientific letters of the University of Zilina, 2019)
In this article, the electrical properties, as well as the economic aspects of the modular and non-modular solution of the DC-DC photovoltaic converter for DC microgrid subsystem, are described. Principally a theoretical overview of the circuit configuration for the selected DC-DC stage of the DC microgrid system is shown. It is dealt with the comparison of the one non-modular high - voltage SiC-based dual - interleaved converter operating at the low switching frequency and with modular low voltage GaN-based DC-DC converters operating at high switching frequencies. The main focus is given to the research of the dependency that arises from the different module count, overall efficiency, costs, and power density (system volume). High efficiency, reduced overall volume, and maximum power density are important factors within modern and progressive solar systems. It is assumed that with the increase of switching frequency within the modular system the volume reduction of the passive components will be highly demanded, thus PCB dimensions and overall volume can be reduced. This dependency is investigated, while the total volume of the non-modular system is a unit of the measure. For these purposes, the design of variant solution was done, and consequently mutually compared in the way of simulations and experimental measurements.